1974
DOI: 10.1002/tera.1420090308
|View full text |Cite
|
Sign up to set email alerts
|

Single umbilical artery with caudal defects in human fetuses

Abstract: Single umbilical artery associated with multiple anomalies is described in three stillborn human fetuses. Detailed study of the abdominopelvic arteries showed replacement of the abdominal aorta below the origin of the superior mesenteric artery by the umbilical artery in all three specimens. This finding greatly helps in solving the age-old riddle of the cause-effect relation between the umbilical anomaly and its associated defects. Single umbilical artery can give rise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…This vascular malformation is identical to that invariably observed in sirenomelia, which has been regarded by others as a pathogenetically distinctive difference between caudal regression and sirenomelia [Stevenson et al, 1986; Twickler et al, 1993; Jones, 1997; Valenzano et al, 1999; Das et al, 2002]. A review of the literature identified four other cases of caudal regression with abdominal umbilical arteries (Tables II and III) [Chaurasia, 1974; Perez‐Aytes et al, 1997]. Collectively, these cases show that an aberrant umbilical artery occurs in both sirenomelia and caudal regression.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This vascular malformation is identical to that invariably observed in sirenomelia, which has been regarded by others as a pathogenetically distinctive difference between caudal regression and sirenomelia [Stevenson et al, 1986; Twickler et al, 1993; Jones, 1997; Valenzano et al, 1999; Das et al, 2002]. A review of the literature identified four other cases of caudal regression with abdominal umbilical arteries (Tables II and III) [Chaurasia, 1974; Perez‐Aytes et al, 1997]. Collectively, these cases show that an aberrant umbilical artery occurs in both sirenomelia and caudal regression.…”
Section: Discussionmentioning
confidence: 57%
“…This aberrant vessel is the basis for the hypothesis that sirenomelia results from “vascular steal”, diversion of blood away from the caudal embryo through the ectopic umbilical artery [Stevenson et al, 1986]. Although similar umbilical arterial anatomy has been described in four cases of non‐sirenomelic caudal regression, the significance of these reports has not been adequately appreciated [Chaurasia, 1974; Perez‐Aytes et al, 1997]. Instead, the presence/absence of an aberrant umbilical artery remains central to the concept that sirenomelia and caudal regression are pathogenetically distinct.…”
Section: Introductionmentioning
confidence: 99%
“…Palacios and Rodriguez (1990) described vascular steal in LBWD in 1990. Chaurasia (1974) reported three stillborn infants with caudal malformations and single umbilical arteries of vitelline origin. Several anomalies in the first infant (imperforate anus, cystic kidney, cardiac defect) would justify the designation VACTERL association and the anomalies in infant 2 (omphalocele, exstrophy of the cloaca, imperforate anus) could represent OEIS complex.…”
Section: Discussionmentioning
confidence: 99%
“…The type I IUA is normally associated with such severe defects that it is usually described only in a fetus [1,11,12]. It is closely associated as part of a caudal regression – sirenomelia spectrum, which is probably caused by an embryonic deficiency of the caudal mesoderm [1].…”
Section: Discussionmentioning
confidence: 99%